Immunological implications of pregnancy-induced microchimerism - Kinder, Jeremy M. (Nat Rev Immunol, 2017)
Immunological identity is traditionally defined by genetically encoded antigens, with equal maternal and paternal contributions as a result of Mendelian inheritance. However, vertically transferred maternal cells also persist in individuals at very low levels throughout postnatal development. Reciprocally, mothers are seeded during pregnancy with genetically foreign fetal cells that persist long after parturition. Recent findings suggest that these microchimeric cells expressing noninherited familially relevant antigenic traits are not accidental souvenirs of pregnancy, but are purposefully retained within mothers and their offspring to promote genetic fitness by improving the outcome of future pregnancies. Here, we discuss the immunological implications, benefits and potential consequences of individuals being constitutively chimeric with a biologically active ‘microchiome’ of genetically foreign cells.